ANALISA PENGGUNAAN SILICON CONTROLLED RECTIFIER PADA ELEKTROPLATING TEMBAGA/BAJA KARBON RENDAH - Prasetia, Vicky; Permana T, Roy Aries (Politeknik Negeri Cilacap, 2019)
Electroplating is one of the engineering improvements in the characteristics of metal materials. Copper coating is a pre-coating before further coating for steel. The surface area of the material is in line with the strong current requirements required for the normal coating process. However, too much current flowing into the cathode results in erosion at the anode. Silicon Controlled Rectifier (SCR) is a component made of semiconductor silicon. It has a function as a controller or switch. Silicon Controlled Rectifiers can be used to reduce coating currents in copper electroplating. The setting of the coating current can be done on copper electroplating of low carbon steel cathodes with a cross-sectional area of 7500 mm2 of 4.5 A; 5 A; 6 A; 6.5 A and 6.7 A. The best copper coating results with a 10 minute coating time are shown in the current 6.5 A with a coating mass of 1.11 grams and 1.06 grams. This proves the need for a reduction in the maximum flow so that optimal coating is achieved.